2009
DOI: 10.1111/j.1365-2672.2008.04031.x
|View full text |Cite
|
Sign up to set email alerts
|

Legionellapollution in cooling tower water of air-conditioning systems in Shanghai, China

Abstract: Aims:  To determine Legionella pollution prevalence, describe the amount of Legionellae with respect to temperature in Shanghai cooling tower water (CTWs) in various types of public sites. Methods and Results:  Six urban districts were selected as the study fields, adopting multiple‐phase sampling methods. Routine culture was used to identify Legionellae. Of the samples, 58·9% (189/321) were observed to be positive, 19·9% were isolated over 100 CFU ml−1. Legionella pneumophila serogroup 1 was the most frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
10
3
Order By: Relevance
“…The Legionella pollution and concentration were also different between seasons in this study: the levels were higher in spring and winter but lower in summer and autumn. In another study that looked at cooling towers in China, the highest isolation rate and concentration was observed in autumn and showed a positive association between Legionella presence in cooling towers and increasing air temperatures [15]. However, in this study, the association between the presence of Legionella in spring water samples and increasing air temperatures was negative.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The Legionella pollution and concentration were also different between seasons in this study: the levels were higher in spring and winter but lower in summer and autumn. In another study that looked at cooling towers in China, the highest isolation rate and concentration was observed in autumn and showed a positive association between Legionella presence in cooling towers and increasing air temperatures [15]. However, in this study, the association between the presence of Legionella in spring water samples and increasing air temperatures was negative.…”
Section: Discussioncontrasting
confidence: 74%
“…The water systems of artificial facilities, including potable water systems [8], [9], spa water [10] and cooling towers [11], [12] in large buildings, hotels, hospitals and public baths that are contaminated by Legionella are the implicated sources of outbreaks and sporadic cases of Legionnaires' disease. Thus, it is important from a public health perspective to continually survey environmental water systems for the presence of Legionella [13], [14], [15], [16]. In particular, the contamination of hot-water systems has gradually become recognized as an important risk factor all over the world [17], [18], [19], [20], [21], [22], and many cases of Legionnaires' disease have been detected in Legionella -contaminated hot-water systems.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental reservoirs of Legionella are ground water, lakes and rivers [1], [2]; Legionella , however, was also isolated from potting soils and composts [3], [4], [5]. Most LD infections are linked to contaminated hot water systems, cooling towers [6], and air-conditioning systems [7], but LD cases related to potting soil use or gardening have also been described [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study that compared the efficacy of different Legionella detection methods, we isolated Legionella at rates of 26.39%, 54.44%, and 18.94% from cooling towers, hot springs, and piped water systems, respectively, with Legionella concentrations of Ͼ1,000 CFU/liter (15). Studies have reported that L. pneumophila serogroup 1 is the most frequently isolated species in cooling towers and hot springs (9,11).…”
mentioning
confidence: 99%
“…Transmission of bacteria from the environment to humans occurs via inhalation or aspiration of Legionella-containing aerosols (7,8). Cooling towers (9,10), hot springs (11,12), and potable water systems (13,14) in large facilities, hotels, hospitals, and public baths that are contaminated with Legionella are the implicated sources of outbreaks and sporadic cases of Legionnaires' disease.…”
mentioning
confidence: 99%